Javan Rhino (Rhinoceros sondaicus Desmarest 1822) Utilization Distribution and Habitat Selection in Ujung Kulon National Park - Santosa, Yanto; Rahmat, U Mamat; Prasetyo, Lilik Budi; Kartono, Agus Priyono (Jurnal Manajemen Hutan Tropika, 2013)
Javan rhino (Rhinoceros sondaicus Desmarest 1822) is one of world's rarest endangered species (IUCN 2008). Currently,  their distribution  is  limited  to Ujung Kulon National Park  (UKNP) of  Indonesia. Natural disasters, disease, poaching, encroachment, and competition are threats  facing Javan rhino's population, hence creating pockets of habitats outside  the UKNP was necessary and  should be based on  scientific  studies of  javan  rhino utilization distribution and habitat selection in UKNP as the natural habitat. The objectives of the study were to determine  the utilization distribution of Javan rhino and  its habitat characteristics and determine  javan rhino habitat selection within UKNP.  The research  indicated  that Javan rhinos highest use of areas comprised of swampy shrub (w = 2.197) and shrub (w = 2.012), relatively open habitat (w = 4.233), flat area (w = 1.313) and slightly sloping areas (w = 1.007), lowland (w = 1.346), close to river (w = 1.087), close to road network (w = 1.395), close to coasts/beaches (w = 1.862), close  to wallowing areas (w = 3.709), and close  to rumpang (w = 3.783).  The results suggested  that  javan  rhino  showed  selection and preferences  for  its habitat.